Dying in Darkness: Deviations From Data Sharing Ethics in the US Public Health System and the Data Genocide of American Indian and Alaska Native Communities - Cason D Schmit; Meghan Curry O’Connell; Sarah Shewbrooks; Charles Abourezk; Fallon J Cochlin; Megan Doerr; Hye-Chung Kum (Journal of Medical Internet Research)
Tribal governments and Tribal Epidemiology Centers face persistent challenges in obtaining the public health data that are essential to accomplishing their legal and ethical duties to promote health in American Indian and Alaska Native communities. We assessed the ethical implications of current impediments to data sharing among federal, state, and Tribal public health partners. Public health ethics obligates public health data sharing and opposes data collection without dissemination to affected communities. Privacy practices, like deidentification and data suppression, often obstruct data access, disproportionately affect American Indian and Alaska Native populations, and exacerbate health disparities. The 2020-2024 syphilis outbreak illustrates how restricted data access impedes effective public health responses. These practices represent a source of structuralized violence throughout the US public health system that contributes to the data genocide of American Indian and Alaska Native populations. Good governance practices like transparent data practices and the establishment of a social license (ie, the informal permission of a community to collect and use data) is essential to ethically balancing collective well-being with individual privacy in public health.